2020
DOI: 10.1002/er.6192
|View full text |Cite
|
Sign up to set email alerts
|

Solar‐powered microwave pyrolysis of corn stover for value‐added products and process techno‐economic assessment

Abstract: Microwave pyrolysis, powered by the solar photovoltaic (PV) electricity has been studied for safe and effective disposal of one of the abundantly available agro-residues that is, corn stover (CS) in India. The study focuses on maximizing the yields of value-added products that is, wood vinegar and biochar, because of their several applications in the agriculture and easy trading among the farmers with a scope of earning higher economic benefits. The effects of different levels microwave power, reaction time, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…The current study used a modified domestic microwave oven (LG, 28 L convection oven) with a 1-L cylindrical quartz reactor. The diagram of the experimental set-up, as well as other essential information on the experimental set-up and procedures followed, are detailed in our previous work 28 – 30 . Based on our prior work 4 , the experiments were conducted under different microwave powers of 500, 700, and 900 W and different ratios of AC additive (10, 20, and 30%) with a constant reaction time of 15 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study used a modified domestic microwave oven (LG, 28 L convection oven) with a 1-L cylindrical quartz reactor. The diagram of the experimental set-up, as well as other essential information on the experimental set-up and procedures followed, are detailed in our previous work 28 – 30 . Based on our prior work 4 , the experiments were conducted under different microwave powers of 500, 700, and 900 W and different ratios of AC additive (10, 20, and 30%) with a constant reaction time of 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…For the calculation of the quantity of CO 2 emissions, it has been reported that about 1.5 kg of CO 2 is emitted into the environment by burning 1 kg of CS feedstock 1 , 2 . This quantity of CO 2 can be mitigated by applying the MAP process for the safe disposal of agricultural wastes like CS 28 , 29 . In addition, the coal-based thermal power plant generally produces about 0.98 kg of CO 2 /kWh.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modified domestic microwave oven (LG, 28 L convection oven), with 1-liter cylindrical quartz reactor was used in the current study. The microwave oven was operated at 2.45 GHz frequency with a maximum input power of 1200 W. 27 Figure 1 presents the diagram of the experimental set-up and other relevant information about the experimental set-up and the procedures followed as described in detail in our previous work. 34 A fixed amount of 60 g of feedstock without or with additive (10% of feedstock) was introduced into the reactor.…”
Section: Experimental Set-up and Proceduresmentioning
confidence: 99%
“…26 Thus, only the chemical energy and exergy have been included in the current study based on calorific values for bio-oil and biochar. 27 On the other hand, the bio-oil produced from MAP of CS has low quality in terms of low calorific value, 28 high oxygen contents 29 and poor chemical composition. 30 Also, biochar needs more improvements 31 in terms of improving its calorific 32 and its elemental composition.…”
Section: Introductionmentioning
confidence: 99%